Thinking Ulumul Qur'an Kh. Muntaha Al-hafidz: A Study Tahqiqi/Philological And Content Analysis Of The Book Abhar Al-quran - Khoirul Muhtadin; Amin Mukrimun; Lilik Rochmad Nurcholisho; M Fawwaz (Universitas Muhammadiyah Surakarta, 2024)
Journal of Quran and Tafseer Studies Volume 2 No.2 Page (203-219)